Respiratory Infection Caused By Chlamydophila pneumonia in Children. Approaches to Diagnosis and Treatment - Ye.I. Yulish; S.G. Gadetskaya; S.I. Vakulenko; V.S. Kolesnikova (Zaslavsky O.Yu., 2013)
The article presents the data on the incidence of respiratory chlamydia infections in children with acute and chronic respiratory diseases. There have been described the features of the course of these diseases secondary to respiratory chlamydia infection. The methods of diagnosis and treatment of various forms of chlamydia infection caused by Chlamydophila pneumonia in children with respiratory pathologies are considered.